Paradoxical response inhibition advantages in adolescent obsessive compulsive disorder result from the interplay of automatic and controlled processes - Wolff, Nicole (Neuroimage Clin, 2019)
Response inhibition deficits have often been described in obsessive compulsive disorder (OCD). Yet, research on response inhibition in OCD focusses on “top-down” controlled mechanisms, and it has been neglected that response inhibition performance depends on the interplay of controlled and automatic processes during response selection. Based on pathophysiological considerations we test the counterintuitive hypothesis that OCD patients show superior inhibitory control when automatic mechanisms govern processes involved in response inhibition. We examined a group of adolescent OCD patients (n = 27) and healthy controls (n = 27) using a combined Simon-Go/NoGo task. This task is able to examine conjoint effects of automatic and controlled processes during response inhibition. EEG and source localization analyses were applied to examine the underlying neural mechanisms. OCD patients committed fewer false alarms than healthy controls (HC) in the congruent Simon-NoGo condition, which is dominated by automatic response selection mechanisms. On a neurophysiological (EEG) level, these effects were reflected by intensified correlates of ‘braking’ processes associated with modulation of right inferior prefrontal regions. There is no general response inhibition deficit in adolescent OCD. When considering conjoint effects of automatic and controlled processes during the inhibition of responses paradoxical response inhibition advantages can emerge in OCD. This is likely a result of otherwise pathological fronto-striatal hyperactivity and loss of a situation-specific modulation of response selection mechanisms in OCD.